Vanillin from food flavoring products as a cheaper alternative hydrophilic agent for modifying PVDF membranes in the treatment of organic compounds in water - Nurbayani, Nurbayani; Ambarita, Aulia; Mulyati, Sri (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Membrane fouling is an unavoidable challenge in ultrafiltration, resulting in reduced flux and increased operating costs. Surface modification of polyvinylidene fluoride (PVDF) membranes can improve hydrophilicity and extend membrane lifetime. This study investigates vanillin from food flavoring product (VFFP) as a hydrophilic additive for PVDF membranes to enhance antifouling properties. The immersion precipitation phase inversion method was used to prepare membranes with 0-3% (w/w) vanillin. The results of FTIR analysis of VFFP show similarity in absorption peaks with commercial vanillin. The addition of 3% w/w VFFP to PVDF membrane can improve the hydrophilicity by reducing the contact angle from 86 to 76.26. Membrane performance showed good results with modified membranes having higher water fluxes than unmodified membranes. In addition, higher flux recovery ratio (FRR) values indicated better antifouling properties.The addition of vanillin significantly improved the performance of PVDF membranes, confirming its use as a hydrophilic additive.